The micro-curricular planning and the classroom management of the english language with the students of 1st 2nd and 3rd years of bachillerato at ―unidad educativa anexa a la Universidad Nacional de Loja‖. Academic year 2012-2013 - Saritama Díaz, Rosa Susana (2014)
The present research work entitled: THE MICRO-CURRICULAR PLANNING AND THE CLASSROOM MANAGEMENT OF THE ENGLISH LANGUAGE WITH THE STUDENTS OF 1st, 2nd AND 3rd YEARS OF BACHILLERATO AT ―UNIDAD EDUCATIVA ANEXA A LA UNIVERSIDAD NACIONAL DE LOJA‖. ACADEMIC YEAR 2012-2013 has been made with the purpose of determining how the micro-curricular planning influences the classroom management of the English Language classroom. In order to undertake this research, the scientific method was used to find the facts about the researched object through a contrast between theory and reality. The survey technique was selected for gathering the information, and it was applied to teachers and students of the researched institution. The main conclusions were that the teachers are not applying sufficient strategies or activities in micro-curriculum planning and classroom management of the English Language classroom.